Faktor–Faktor Yang Mempengaruhi Manajemen Pendidikan - Ahmad Ridwan; Aulia Afriani Lestari; Aunia Afriani Lestari; Muhammad Almansyawwi; Wahyudin Wahyudin (Lembaga Pengembangan Kinerja Dosen, 2025)
Education management is the process of managing educational resources to achieve educational goals effectively and efficiently. To realize quality education management, it is necessary to understand the various internal and external factors that influence the management process of educational institutions. This article comprehensively discusses these factors, including leadership, teaching staff, students, facilities and infrastructure, financing, curriculum, school culture, technology, and government policies. The discussion is based on a literature review of educational management books that have been scientifically recognized. The results of the study show that the success of educational management is not determined by a single factor, but is the result of a complex interaction of various components. It is hoped that this article can become an academic reference for educational practitioners, researchers and policy makers